2021
DOI: 10.1186/s12889-021-10170-8
|View full text |Cite
|
Sign up to set email alerts
|

Financial burden impact quality of life among lymphatic Filariasis patients

Abstract: Background Human lymphatic filarial pathology is the leading cause of disability and poverty among people living with the infection. The second goal of the Global Programme to Eliminate Lymphatic Filariasis (GPELF) is to manage the disease’s morbidity to improve patients’ quality of life. Consequently, the current study assessed the overall quality of life of lymphatic filariasis (LF) pathology patients in some selected endemic communities in rural Ghana. Method … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Previously, we have shown a positive correlation of the disease burden and pain or discomfort [ 39 ]. In managing the pain and skin peelings (as measures for morbidity management), LF patients resort to the use of antibiotics for self-medication as a preferred alternative to travelling long distance and the cost in accessing primary healthcare [ 5 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have shown a positive correlation of the disease burden and pain or discomfort [ 39 ]. In managing the pain and skin peelings (as measures for morbidity management), LF patients resort to the use of antibiotics for self-medication as a preferred alternative to travelling long distance and the cost in accessing primary healthcare [ 5 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…We anticipate these observations on knowledge and adherence in Bangladesh and Ethiopia will be useful to other endemic countries with similar populations. It is well documented that people affected by lymphedema at all stages have impaired qualify of life and increased financial pressures (34), and that introduction of a hygiene centered self-care program can improve symptoms and reduce ADL episodes (11,12). In our study, people affected by moderate and severe lymphedema and their caregivers were able to learn and apply lymphedema self-care with a high level of adherence over 24-weeks.…”
Section: Discussionmentioning
confidence: 66%
“…Wuchereria bancrofti -driven immunomodulation is a key feature of this helminth’s survival and homeostasis of host’s immune responses to maintain an asymptomatic disease state ( Hoerauf et al., 2005 ; Babu et al., 2006 ; Babu et al., 2009 ; Adjobimey and Hoerauf, 2010 ; Babu and Nutman, 2012 ; Wammes et al., 2012 ; Rajamanickam and Babu, 2013 ; Metenou et al., 2010 ; Ritter et al., 2019 ). However, severe clinical outcomes such as LE can lead to increased DALYs and social stigmatisation ( Gyapong et al., 1996 ; van 't Noordende et al., 2020 ; World Health Organization, 2021 ; World Health Organization, 2020 ; Asiedu et al., 2021 ). Several studies already characterized CD4 + T cells in LE patients and revealed that frequencies of naive, effector memory and central memory CD4 + T cells in patients with filarial disease and chronic infections were not different.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the tightly controlled immune-regulation, individuals with LF can also develop severe symptoms like hydrocele or lymphedema (LE) as well as adenolymphangitis (ADL) attacks ( World Health Organization, 2020 ; World Health Organisation 2021 ). This often leads to reduced quality of life and increased disability-adjusted life years (DALYs), financial losses, and social separation due to the stigmatization ( Gyapong et al., 1996 ; van 't Noordende et al., 2020 ; Asiedu et al., 2021 ). Interestingly, the majority of patients suffering from severe pathology have usually cleared the infection and their profiles are characterized by increased antigen-specific Th1 and Th17 responses and constant immune activation ( Babu et al., 2009 ; Babu and Nutman, 2012 ; Babu and Nutman, 2014 ).…”
Section: Introductionmentioning
confidence: 99%